Meaning as Motivator to Address Distancing in the Food System - Karen Rideout (Canadian Food Studies, 2021)
Distancing in the food system prevents people from having full knowledge and making informed choices about what and how they produce, exchange, prepare, and eat food. This becomes problematic when the dominant industrial food system contributes to myriad negative human health, ecological, and social outcomes. This paper reports on findings from a study that aimed to better understand distancing from the perspectives of people engaged in resisting it, focusing on their motivations for action to inform policy approaches to improve food system health. The research, conducted in India and Canada, comprised participant observation with organizations working to connect the production and consumption of food, as well as interviews with activists, consumers, and farmers involved with those organizations. These food system actors were motivated primarily by a conviction that food is important, which was illustrated by meaningful relationships built and maintained through food, by soulful connections with food, and by a sense that everything – including food – is interconnected. The findings identify connection around food as a source of meaning in life. From meaning comes awareness of broader issues, a sense of value and care, and ultimately motivation for action or change. This could have implications for healthy food system governance if frameworks such as determinants of health and healthy food environments are used to inform healthy public policies that cultivate a sense of meaning and awareness of the intrinsic value embedded in food.